The Great Leveler: Gender and the Institutionalized Disabled on Faith and Disability - Meakes, Elizabeth (Journal of religion, disability & health, 2002)
Gender similarities and differences are examined among disabled persons who are institutionalized using an ethnographic study already published (O'Connor et al., 1998). The sample in the study is 26 participants with 16 being female and 10 being male. Gender differences arise around the importance of relationships and the experience of the wheelchair. There is a lack of awareness of patriarchy, and both genders view a radical difference between disabled and able bodied, and not between the genders. Both genders fight for justice and use non-gender specific language to describe God. Disability in this sample tends to produce a level playing field between the genders.